A Conceptual Model of Integrating Deliberative Transformative and Authentic Learning in Multicultural Religious Education - Irfan Musonif; Muhammad Misbah (Penerbit Hellow Pustaka, 2026)
This study aims to develop an integrative conceptual framework for religious education that addresses the challenges of multicultural societies by synthesizing deliberative learning, transformative learning, and authentic learning. Employing a qualitative library research approach, this study utilizes interpretive thematic synthesis to analyze relevant scholarly literature. The findings reveal that these three approaches form interconnected epistemological relationships while also containing inherent conceptual tensions, particularly between rational dialogue, critical reflection, and real-life contextual experience. The synthesis results in the formulation of the Integrative Deliberative–Transformative–Authentic Religious Learning Model (IDTARL), a cyclical framework in which deliberative dialogue triggers cognitive dissonance, critical reflection facilitates meaning transformation, and authentic experience serves as a space for validation and reconstruction of understanding. The study demonstrates that effective religious learning in multicultural contexts is not determined by a single pedagogical approach but by a balanced integration of dialogic, reflective, and contextual dimensions. Theoretically, this research contributes to reconstructing the epistemology of religious education from a transmission-oriented paradigm toward a dialogic–reflective–contextual paradigm that is more responsive to multicultural realities.